2013
DOI: 10.1007/s00216-013-7133-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of electrochemically and in vitro biologically generated oxidation products of atorvastatin using UHPLC/MS/MS

Abstract: Ultrahigh-performance liquid chromatography coupled with high-mass-accuracy tandem mass spectrometry (UHPLC-MS-MS) has been used for elucidation of the structures of oxidation products of atorvastatin (AT), one of the most popular commercially available drugs. The purpose of the study was identification of AT metabolites in rat hepatocytes and comparison with electrochemically generated oxidation products. AT was incubated with rat hepatocytes for 24 h. Electrochemical oxidation of AT was performed by use of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The mechanism was not discussed, however, and for verapamil and toremifen could actually be ipso-substitution. Electrochemical oxidation has resulted in product profiles very similar to those of in vivo and in vitro metabolism (Baumann et al, 2009), but also considerable differences have been reported (Jirasko et al, 2013;Johansson et al, 2007).…”
Section: Introductionmentioning
confidence: 92%
“…The mechanism was not discussed, however, and for verapamil and toremifen could actually be ipso-substitution. Electrochemical oxidation has resulted in product profiles very similar to those of in vivo and in vitro metabolism (Baumann et al, 2009), but also considerable differences have been reported (Jirasko et al, 2013;Johansson et al, 2007).…”
Section: Introductionmentioning
confidence: 92%